The Safety Explorer Suite: Interactive Safety Monitoring for Clinical Trials. (November 2018) - Wildfire, Jeremy; Bailey, Ryan; Krouse, Rebecca Z.; Childress, Spencer; Sikora, Britt; Bryant, Nathan; Rosanbalm, Shane; Wilson, Emily; Modell, Jack G.
Background: Frequent and thorough monitoring of patient safety is a requirement of clinical trials research. Safety data are traditionally reported in a tabular or listing format, which often translates into many pages of static displays. This poses the risk that clinically relevant signals will be obscured by the sheer volume of data reported. Interactive graphics enable the delivery of the vast scope of information found in traditional reports, but allow the user to interact with the charts in real time, focusing on signals of interest. Methods: Clinical research staff, including biostatisticians, project managers, and a medical monitor, were consulted to guide the development of a set of interactive data visualizations that enable key safety assessments for participants. The resulting "Safety Explorer" is a set of 6 interactive, web-based, open source tools designed to address the shortcomings of traditional, static reports for safety monitoring. Results: The Safety Explorer is freely available on GitHub as individual JavaScript libraries: Adverse Event Explorer, Adverse Event Timelines, Safety Histogram, Safety Outlier Explorer, Safety Results Over Time, and Safety Shift Plot; or in a single combined framework: Safety Explorer Suite. The suite can also be utilized through its R interface, the safetyexploreR package. Conclusions: The Safety Explorer provides interactive charts that contain the same information available in standard displays, but the interactive interface allows for improved exploration of patterns and comparisons. Medical Monitors, Safety Review Boards, and Project Teams can use these tools to effectively track and analyze key safety variables and study endpoints.